2016
DOI: 10.1097/ta.0000000000001017
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of platelet function in trauma patients

Abstract: Prognostic and epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 26 publications
0
57
3
1
Order By: Relevance
“…Staining was performed according to the microscopy procedure (above). Forward scatter (FSC) signal, assumed to be proportional to cell size or cell volume, and side scatter (SSC) signal, related to the complexity of the cell (Ramsey et al, 2016), were collected and plotted against fluorescence from BODIPY 505/515 in the FITC-A channel.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Staining was performed according to the microscopy procedure (above). Forward scatter (FSC) signal, assumed to be proportional to cell size or cell volume, and side scatter (SSC) signal, related to the complexity of the cell (Ramsey et al, 2016), were collected and plotted against fluorescence from BODIPY 505/515 in the FITC-A channel.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…[12][13][14]36 Henriksen et al 26 showed that although platelet aggregation function declined over time after admission in severely injured patients, it was further reduced in those patients receiving blood products, with platelet transfusion associated with the most dramatic reduction in function. One potential proposed mechanism for this is the known poor platelet function of stored platelets.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Given the importance of endogenous platelets to hemostasis and their observed inability to function appropriately in severely injured patients, early platelet transfusions would seem intuitive. [12][13][14] Several retrospective studies and metaanalyses have demonstrated a benefit of platelet transfusions on outcomes in trauma patients. [15][16][17][18][19] These data are supported by 2 multicenter, prospective observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma-induced coagulation defect is a severe co-morbidity, strongly associated with an increased mortality [26]. Early therapy might also include platelet-directed treatments [27, 28]. …”
Section: Discussionmentioning
confidence: 99%